Materi Bimbingan Rohani Islam di Rumah Sakit (Studi terhadap Pandangan Pembina Rohani di Rumah Sakit Muhammadiyah Bandung) - Deva Awaludin (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
Islamic spiritual guidance is an activity of providing assistance to clients or who can also be called patients, or families to improve their spirituality. According to Islam, maintaining balance in life requires nurturing the soul, mind and body. This is also applied to someone who is suffering from an illness in the hope that the spiritual person will be able to help recover from the illness he is suffering from. Muhammadiyah Bandung Hospital, is one of the hospitals that has a spiritual guidance program to strengthen the faith of a patient, and his family. In this study, researchers used qualitative methods with the type of field research (field research). Data obtained through interviews, and other supporting data. The results of this study provide an overview of the very large effectiveness of the spiritual guidance materials applied at the Bandung Muhammadiyah Hospital. The Spiritual Guidance Officer has succeeded in restoring mentality and developing the spirit of health as well as motivating the health of individual patients in the hospital. All services carried out such as psychological services, spiritual services, manual assessment of psychospiritual status sheets, guiding patients in the sakaratul maut, to bathing and revolving corpses have been carried out effectively and very well at the Muhammadiyah Hospital in Bandung.